2018
DOI: 10.1016/j.jid.2018.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes Support the Degradation, Signaling, and Mitochondrial Metabolism Necessary for Human Epidermal Differentiation

Abstract: Keratinocytes undergo significant structural remodeling during epidermal differentiation, including a broad transformation of the proteome coupled with a reduction in total cellular biomass. This suggests that intracellular digestion of proteins and organelles is necessary for keratinocyte differentiation. Here, we use both genetic and pharmacologic approaches to demonstrate that autophagy and lysosomal functions are required for keratinocyte differentiation in organotypic human skin. Lysosomal activity was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 57 publications
0
68
0
Order By: Relevance
“…Additionally, vimentin, as well as keratin intermediate filaments, have been shown to move along microtubules with the help of KIF5B . Furthermore, it has recently been shown that autophagy and lysosomal functions play an important role in keratinocyte differentiation in organotypic human skin where lysosomes promote mitochondrial metabolism and the associated production of mitochondrial ROS, which in turn triggers autophagy on its release into the cytoplasm of suprabasal keratinocytes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, vimentin, as well as keratin intermediate filaments, have been shown to move along microtubules with the help of KIF5B . Furthermore, it has recently been shown that autophagy and lysosomal functions play an important role in keratinocyte differentiation in organotypic human skin where lysosomes promote mitochondrial metabolism and the associated production of mitochondrial ROS, which in turn triggers autophagy on its release into the cytoplasm of suprabasal keratinocytes …”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, it has recently been shown that autophagy and lysosomal functions play an important role in keratinocyte differentiation in organotypic human skin where lysosomes promote mitochondrial metabolism and the associated production of mitochondrial ROS, which in turn triggers autophagy on its release into the cytoplasm of suprabasal keratinocytes. 44 Autolysosomal reformation is upregulated during stress situations; it depends on mTOR signalling and can be blocked by the mTOR inhibitor rapamycin. 15,45 In contrast, rapamycin treatment also induces autophagy, providing a feedback mechanism to avoid excessive cell-harming autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…AKT phosphorylation at conserved RXXS/T motifs Lysosomes are critical for the degradation of cellular macromolecules and are transcriptionally regulated by MiT/TFE family members. Interestingly, upregulation of lysosomal function as well as mTORC1 activation are independently essential for epidermal differentiation and barrier function (18,31). However, the interdependence of mTOR signaling and lysosomal function has not been studied in the skin.…”
Section: Inhibition Of Hyperactive Akt In Mtorc1-inhibited Cells Rescmentioning
confidence: 99%
“…As a first step to understanding how mTORC1 regulates MiT/TFE activity, we studied isogenic normal cells with or without genetic perturbations leading to constitutive or abrogated mTORC1 signaling. The epidermis and primary keratinocyte cultures provide a unique and well-characterized epithelial model system where the lysosome plays an important role in cellular differentiation and homeostasis (18), thus we developed genetically engineered mouse models of Tsc1, Rheb, or Rptor conditional deletion in the epidermis. Herein, we demonstrate that in the context of long-term, bidirectional mTORC1 signaling perturbation, mTORC1 feedback to AKT prevails to regulate MiT/TFE levels and lysosomal biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise regulation and order of degradative events remain to be determined, a critical role of lysosomes in cornification can be assumed. [16] In particular, the involvement of the lysosomal DNase 2 [15] suggests that the content of lysosomes (including a multitude of degradative enzymes) is released to the cytoplasm and also gains access to components of the nucleus.…”
Section: Intrinsic Danger Signaling and Its Suppression By Inhibitorsmentioning
confidence: 99%